Production of Napoli salami from some autochthonous pig genetic types. I. Rheological and colour characteristics - Cappuccio A.; Santopietro V. (Tradition and innovation in Mediterranean pig production, 2000)
The research was carried out on 'Napoli' salami obtained using separable meat, excluding neck and ham, from castrated males and whole females belonging to Calabrese, Cinta senese and Siciliano autochthonous genetic types. The rheological and colour characteristics were evaluated on salami seasoned in two different plants (Angri and Morcone) for 45 d and subsequently stored for 45 and 135 d, partly in a vacuum and partly under kidney fat. The results evidenced that on average: (i) in comparison with Cinta senese, Siciliano provide a more tender salami, with a lower adhesiveness, requiring a lower chewing energy and with a lower red index (a*) (P less than 0.001); (ii) salami seasoned in Morcone, if compared to that from Angri, is more tender and requires a lower chewing energy (P less than 0.001); (iii) females provide a salami characterized by a higher adhesiveness (P less than 0.05) and hue percentage (P less than 0.001); and (iv) ranging from 45 d to 135 d of storage, both under vacuum and kidney fat, salami becomes harder and requires a higher chewing energy.
4. International Symposium on Mediterranean Pig, 1998/11/26-28, Evora (Portugal)